The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22189805
|View full text |Cite
|
Sign up to set email alerts
|

Optimised Heterologous Expression and Functional Analysis of the Yersinia pestis F1-Capsular Antigen Regulator Caf1R

Abstract: The bacterial pathogen, Yersinia pestis, has caused three historic pandemics and continues to cause small outbreaks worldwide. During infection, Y. pestis assembles a capsule-like protective coat of thin fibres of Caf1 subunits. This F1 capsular antigen has attracted much attention due to its clinical value in plague diagnostics and anti-plague vaccine development. Expression of F1 is tightly regulated by a transcriptional activator, Caf1R, of the AraC/XysS family, proteins notoriously prone to aggregation. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…The same result was observed when using another antibody, in this case, an HRP-conjugated anti-his tag antibody, to reveal the membrane (Supplementary Figure S10). The low expression of WT MarA in shuffle T7 express cells is supported by a recent paper in which the authors observed by WB the decline of the signal corresponding to the His-tagged AraC/XylS transcriptional factor Caf1R when inducing in shuffle T7 express cells at 37°C 40 . As the fluorescence signal for WT MarA was high in the reporter system experiment (Figure 3A), we discarded the lack of overexpression of the protein and focused on its degradation.…”
Section: Resultsmentioning
confidence: 56%
“…The same result was observed when using another antibody, in this case, an HRP-conjugated anti-his tag antibody, to reveal the membrane (Supplementary Figure S10). The low expression of WT MarA in shuffle T7 express cells is supported by a recent paper in which the authors observed by WB the decline of the signal corresponding to the His-tagged AraC/XylS transcriptional factor Caf1R when inducing in shuffle T7 express cells at 37°C 40 . As the fluorescence signal for WT MarA was high in the reporter system experiment (Figure 3A), we discarded the lack of overexpression of the protein and focused on its degradation.…”
Section: Resultsmentioning
confidence: 56%
“…MsmR1 is a typical AraC/XylS family transcriptional regulator (Egan, 2002), which can act as activators, repressors, or both, and are involved in various biological processes ranging from metabolism to stress response and virulence (Gahlot et al, 2021). In this study, a ChIP-seq experiment combined with EMSA was performed, the regulatory network of the global regulator MsmR1 was proposed (Figure 7), and the role of MsmR1 in P. polymyxa was described.…”
Section: Discussionmentioning
confidence: 93%
“…Sequence analysis revealed that MsmR1 comprises seven α-helices forming two HTH motifs at the C-terminal domain, which is the DNA binding domain, as well as a sensing or oligomerization domain of approximately 140 amino acids at the N-terminal domain. MsmR1 is a typical AraC/XylS family transcriptional regulator ( Egan, 2002 ), which can act as activators, repressors, or both, and are involved in various biological processes ranging from metabolism to stress response and virulence ( Gahlot et al, 2021 ). In this study, a ChIP-seq experiment combined with EMSA was performed, the regulatory network of the global regulator MsmR1 was proposed ( Figure 7 ), and the role of MsmR1 in P. polymyxa was described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Caf1R protein regulates caf1 expression as part of a complex thermosensitive system that responds to host body temperature [ 26 , 27 ]. To ensure reproducible Caf1 levels we simplified caf1 expression in our assays by deleting caf1R , and so used only basal T7 expression from pT7-COPΔR.…”
Section: Resultsmentioning
confidence: 99%